Portrait of John Abernethy - Macilwain, George (Memoirs of John Abernethy, F.R.S., 1856)
Portrait print of English surgeon John Abernethy (1764-1831). Abernethy invented the Abernethy biscuit as an aid for digestion. He wrote one of the earliest popular works on medical science intended to be read by patients.
Keywords: Abernethy, John, 1764-1831; Medicine--Biography; Portraits